Emerging Issues in Smart Learning
XIV, 397 p. 115 illus.
Keywords: This book provides an archival forum for researchers, academics, practitioners, and industry professionals interested and/or engaged in the reform of the ways of teaching and learning through advancing current learning environments towards smart learning environments. The contributions of this book are submitted to the International Conference on Smart Learning Environments (ICSLE 2014). The focus of this book is on the interplay of pedagogy, technology and their fusion towards the advancement of smart learning environments. Various components of this interplay include but are not limited to: Pedagogy- learning paradigms, assessment paradigms, social factors, policy; Technology- emerging technologies, innovative uses of mature technologies, adoption, usability, standards, and emerging/new technological paradigms (open educational resources, cloud computing, etc.).